If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 18y = 0 Solving 3x + 18y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18y' to each side of the equation. 3x + 18y + -18y = 0 + -18y Combine like terms: 18y + -18y = 0 3x + 0 = 0 + -18y 3x = 0 + -18y Remove the zero: 3x = -18y Divide each side by '3'. x = -6y Simplifying x = -6y
| 12x+3-4x+5=72 | | 6y-(8+y)=4(y-2)+5 | | cos(5x)+cos(2x)+cos(3x)+cos(4x)=0 | | 7=-21-x | | 15x+9y=563 | | 4x=3(x+5) | | 4/2-6*3 | | f(x)=0.5x+7 | | -2=7x-58 | | 14x-6=78 | | Log(3x-8)=0 | | 22=7x-55 | | 4x+22=x-55 | | 12x-25=0 | | 4(3s+2)=104 | | 2(2l+10)=40 | | (-3/7)*x-x | | (3/7)*x-x | | y=9E-05x+0.0926 | | -1x+-1=222+2x | | (-3/7)*x-x=-180 | | -4x-7=43+x | | 2x+9.5=3x | | 7u^2=3m | | Z+1=2(z-2i) | | 3n-87n+624=0 | | 3/7x-x=180 | | 18-4a=3 | | 3ln4/ln3-ln4 | | 7x+17=-18 | | 4x^2-2tx+t=0 | | 15*x=-75 |